Answer:
1.33×10^-6
Step-by-step explanation:
5.32 x 10^-7= 5.32×10^(-5-2)= 5.32×10^-2×10^(-5)
=0.0532×10^-5
(0.0532×10^-5) (2.5 x 10^-5)
0.0532×2.5 × 10^-5
0.133×10^-5= 1.33×10^-1 ×10^-5
1.33×10^-6
Answer:
X=-3/8 (x equals negative 3 over 8.)
Step-by-step explanation:
So, you have twice a number and six. That is going to be 2x*6, and that then simplifies into 12x. Now, 11 times the number, would be 11x. The difference between 11x and 3/8 would be 11x-3/8.
So, You now have 12x=11x-3/8.
Combine like factors. So, 12x-11x=-3/8.
Now, you have x=-3/8.
Hope this Helps!! (:
These triangles are congruent by AAS condition hence the statement is true
Well, accordingly to the graph, it has a positive slope so we can eliminate b and d. So it is either a or c. As x increases, so does y. Y is almost not quite equal to 3x-2. In fact, it is greater, so I'd go with A. I'm pretty confident.
Answer:
?
Step-by-step explanation:
We can't see minor arc xz, you need a picture